Effect of detopping on disease incidence and symptom severity of African cassava mosaic virus disease (ACMD) on some newly developed cassava cultivars form landraces introgression - Ariyo, O.; Atiri, G.; Dixon, A. (2003)
Twenty-five cassava genotypes were exposed to natural infection by African cassava mosaic disease (ACMD) in plots at the International Institute of Tropical Agriculture (IITA), Ibadan (forest-savanna transition zone), Nigeria. The effect of removing the shoot tips (detopping) of cassava plants on disease incidence and symptom severity was assessed fortnightly for 14 weeks, starting 8 weeks after planting (WAP). There were highly significant differences (P < 0.01) in disease incidence (DI) and symptom severity (ISS) among clones throughout the period of observation, indicating different levels of resistance to infection. Detopping produced a significant effect on disease incidence in clones 91/02322, 91/02324, 91/02327 and 92/0427. It also had a significant effect on symptom severity of clones 92/0342, M94/0177 and TMS 4(2) 1425. The interaction between the treatment (TRT) and clone was highly significant (P < 0.01) for DI and ISS throughout the period of observation, an indication that there are differential responses of the clones to detopping. Cassava genotypes M94/0121 and Isu were observed to be highly resistant and highly susceptible respectively to the disease, while plants of genotypes 82/00058 and 91/02322 showed moderate susceptibility. None of the genotypes was immune to the disease. There was also a highly significant and positive correlation between DI and ISS in both detopped and undetopped plants. A conclusion from this study is that removal of shoot tips from moderately resistant cassava clones for consumption should be discouraged as it increases the severity of ACMD infection in the regenerating shoots of these clones